The Implementation of Religious Values Through Singing Activities Among Early Childhood Student at Tk Raudhathul Athfal Soulowe Kab.Sigi - Sukmawati, Sukmawati; Nurhayati, Nurhayati; Amrullah, Amrullah; Agusniatih, Andi (FKIP - Universitas Riau, 2025)
Early childhood is known as the golden age, during which moral, social, and emotional aspects grow rapidly; therefore, appropriate and engaging learning methods are required. Singing was chosen as a learning approach that combines joy and meaningful spiritual learning for children. The purpose of this study is to describe the implementation of religious values through singing activities and to analyze the improvement in children’s religious behavior after participation. This research employed a descriptive qualitative method involving 15 children aged 5–6 years (8 boys and 7 girls) at TK Raudhathul Athfal Soulowe, Sigi Regency. Data were collected through observation and documentation. The learning process was carried out in an enjoyable classroom atmosphere using religious-themed songs such as gerakan berwudhu, gerakan sholat, and berdoa sebelum dan sesudah berkegiatan. These songs were accompanied by simple movements to help children understand and internalize the meanings. The results showed a significant improvement in children’s religious behavior, particularly in performing ablution, prayer movements, and daily prayers. By the fourth week, 33.33% of the children reached the “Very Well Developed” category and 60% were “Developing as Expected.” Overall, singing proved to be an effective and enjoyable method for instilling religious values in early childhood education.